“I am sick, but that’s not all that I am”: patient perspectives on psychological adaptation over time to inborn errors of immunity - Breanna J. Beers; Hannah R. Davidson-Swinton; Katie L. Lewis; Michael R. Setzer; Magdalena A. Walkiewicz; Morgan N. Similuk (Journal of Community Genetics, 2025)
Inborn errors of immunity (IEI) are rare heritable disorders of the immune system predisposing to atypical infections, autoimmunity, inflammation, and risk of malignancy. Adaptation is the process of incorporating stressful experiences into one’s life; these experiences may include onset of illness, receiving a diagnosis, or suffering without a diagnosis. Poor adaptation is linked to adverse outcomes including psychiatric comorbidities and decreased well-being. Most people with chronic illnesses and rare diseases adapt to their condition with time, but little is known about how this happens. We seek to address this gap in knowledge by investigating features of successful adaptation to IEI over time to help providers facilitate this process among those who struggle. We interviewed 20 self-reportedly well-adapted adults with IEI about their experiences of adaptation. We identified three overarching themes. First, many participants grappled with shame and loss but ultimately integrated their illness into their lives through acceptance, gratitude, and self-compassion. Second, knowledge and choice contributed to participants’ perceived control, but most participants were also forced to acknowledge the limits of that control when confronting unpredictable symptoms. Finally, social relationships could influence adaptation either positively or negatively. Notably, many participants found meaning in giving back to their communities, especially by educating others about their condition. Ultimately, participants showed that adaptation to life with IEI is complex and ongoing, requiring frequent recalibration to emerging challenges in new life stages. We provide recommendations to providers to help the results of this study shape their discussions with patients.

Assessment of N-related microbial processes in the soil of the Polesie National Park and adjacent areas, including reclaimed land - J. Joniec; E. Kwiatkowska; A. Walkiewicz; G. Grzywaczewski; A. Garbacz (Journal of Environmental Management, 2025)

Methanotrophs are favored under hypoxia in ammonium-fertilized soils - A. Walkiewicz; M. Brzezińska; A. Bieganowski (Biology and Fertility of Soils, 2018)

Harmonisation of food categorisation systems for dietary exposure assessments among European children - M. De Neve; I. Sioen; P.E. Boon; C. Arganini; J. Moschandreas; J. Ruprich; L. Lafay; P. Amiano; D. Arcella; M. Azpiri; L. Busk; T. Christensen; et al. (Food Additives & Contaminants: Part A, 2010)

Nontuberculous mycobacterial infections among patients suspected of pulmonary tuberculosis - H. Grubek-Jaworska; R. Walkiewicz; A. Safianowska; M. Nowacka-Mazurek; R. Krenke; T. Przybyłowski; R. Chazan (European Journal of Clinical Microbiology & Infectious Diseases, 2009)